Structural engineers attitude and preferences for timber as a building / construction material - Abdul Razak, Ummu Afiqah (2018)
This study was carried out to determine the structural engineer’s attitudes and preferences towards the use of timber as a building/construction material. The main objective of this study was to analyse the attitude and preferences of structural engineers towards the use of timber as a building/construction material. A total of 60 respondents participated in this research of which 34% were males and 26% were females, through to question from a structured questionnaire by online survey form’s link via email. More than half of the respondents have a positive attitude towards timber, especially as a unique and interesting material. However, respondents were also concerned about the price of timber is more expensive than other building materials, prone to attack by pest and its application is limited. Even though the respondents had a positive attitude toward timber but they did not prefer to use timber as their building material. Most of the respondent prefer to use other building material such as brick, concrete, steel and IBS. This survey also shows that preferences of respondents to timber prices have a profound effect on the use of timber as construction materials, especially in decision-making processes, such as the selection of building materials.